Are there multiple mechanisms of anaerobic sulfur oxidation with ferric iron in Acidithiobacillus ferrooxidans? - Kucera, Jiri; Pakostova, Eva; Lochman, Jan; Janiczek, Oldrich; Mandl, Martin (Research in microbiology, 2016)
To clarify the pathway of anaerobic sulfur oxidation coupled with dissimilatory ferric iron reduction in Acidithiobacillus ferrooxidans strain CCM 4253 cells, we monitored their energy metabolism gene transcript profiles. Several genes encoding electron transporters involved in aerobic iron and sulfur respiration were induced during anaerobic growth of ferrous iron-grown cells. Most sulfur metabolism genes were either expressed at the basal level or their expression declined. However, transcript levels of genes assumed to be responsible for processing of elemental sulfur and other sulfur intermediates were elevated at the beginning of the growth period. In contrast, genes with predicted functions in formation of hydrogen sulfide and sulfate were significantly repressed. The main proposed mechanism involves: outer membrane protein Cyc2 (assumed to function as a terminal ferric iron reductase); periplasmic electron shuttle rusticyanin; c4-type cytochrome CycA1; the inner membrane cytochrome bc1 complex I; and the quinone pool providing connection to the sulfur metabolism machinery, consisting of heterodisulfide reductase, thiosulfate:quinone oxidoreductase and tetrathionate hydrolase. However, an alternative mechanism seems to involve a high potential iron-sulfur protein Hip, c4-type cytochrome CycA2 and inner membrane cytochrome bc1 complex II. Our results conflict with findings regarding the type strain, indicating strain- or phenotype-dependent pathway variation.
Keywords: Sulfur metabolism; anaerobióza; Anaerobiosis; Acidithiobacillus ferrooxidans; Anaerobic respiration pathway; oxidace-redukce; Metabolic Networks and Pathways; Ferric iron reduction; Energy Metabolism; Ferric Compounds; energetický metabolismus; stanovení celkové genové exprese; Sulfur; železité sloučeniny; Oxidation-Reduction; metabolické sítě a dráhy; síra; Acidithiobacillus; Gene Expression Profiling; Real-time quantitative PCR